1998
DOI: 10.2337/diacare.21.7.1110
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity of Diabetes and Eating Disorders: Does diabetes control reflect disturbed eating behavior?

Abstract: There seems to be no difference in prevalence rates of EDs in both types of diabetes; however, distribution of EDs is different. The findings suggest that neither EDs nor insulin omission are necessarily associated with poor control of glycemia. Binge eating disorder seems to precede type 2 diabetes in most patients and could be one of the causes of obesity that often precedes type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
59
3
7

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 112 publications
(73 citation statements)
references
References 0 publications
4
59
3
7
Order By: Relevance
“…These results of diabetic patients were in accordance with the literature. [10][11][12] Eating disorders did not show differences with respect to sex.…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…These results of diabetic patients were in accordance with the literature. [10][11][12] Eating disorders did not show differences with respect to sex.…”
Section: Discussionmentioning
confidence: 78%
“…24 They found that bulimia nervosa and eating disorders not otherwise specified were more than twice as common in girls with diabetes compared to controls. The most extensive study investigating eating disorders in diabetic patients was done by Herpertz et al 12 In that study, prevalence range of eating disorders were found as 8% current and 14% lifetime. They found that in those with disordered eating, 60% had binge-eating disorder.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations